2009
DOI: 10.1021/jp8110343
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phosphonic Acid at the TiO2 Anatase (101) and Rutile (110) Surfaces

Abstract: The adsorption of phosphonic acid on the TiO2 anatase (101) and rutile (110) surfaces have been investigated by means of efficient density-functional-based tight-binding calculations. We studied the geometries and adsorption energies of several adsorption models to achieve clarification of the discrepancy in the experimental finding of a preferred binding state. In this paper we show that there are several adsorption structures likely to be present on the specific TiO2 surfaces. Those structures have exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
196
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(218 citation statements)
references
References 124 publications
(291 reference statements)
20
196
0
2
Order By: Relevance
“…The dispersions became unstable again at high ionic strength, since charge screening by the salt constituents occurred. The specific interaction between phosphate anions of different valences and titania particle surfaces has already been observed in other systems too [73][74][75][76]. On the basis of results from experimental (infrared (IR) spectroscopy) and theoretical (efficient density-functional-based tight-binding calculations) methods, it was suggested that a primary chemical bond was established between the metal ions on the surface and the oxygen atom of the phosphate ions and this interaction gives rise to the accumulation of negative charges on the particle surface.…”
Section: Colloids Interfaces 2018 2 X For Peer Review 5 Of 19mentioning
confidence: 59%
See 1 more Smart Citation
“…The dispersions became unstable again at high ionic strength, since charge screening by the salt constituents occurred. The specific interaction between phosphate anions of different valences and titania particle surfaces has already been observed in other systems too [73][74][75][76]. On the basis of results from experimental (infrared (IR) spectroscopy) and theoretical (efficient density-functional-based tight-binding calculations) methods, it was suggested that a primary chemical bond was established between the metal ions on the surface and the oxygen atom of the phosphate ions and this interaction gives rise to the accumulation of negative charges on the particle surface.…”
Section: Colloids Interfaces 2018 2 X For Peer Review 5 Of 19mentioning
confidence: 59%
“…The electrokinetic potentials increased in magnitude by increasing the valence of the anions indicating their adsorption on the like-charged surface. The adsorption of the H2PO4 2− was much stronger compared to the SO4 2− of the same valence due to the specific interaction with the surface metal ions through primary chemical bonds [73][74][75][76]. The stability ratio plots contained slow and fast aggregation regimes separated by the CCIS values, which increased in the SO4 2− < Fe(CN)6 3− < Fe(CN)6 4− < H2PO4 2− order.…”
Section: Multivalent Ion-induced Aggregationmentioning
confidence: 98%
“…Since the differences of the adsorption energies between the different binding motifs are rather small, it is expected that several binding motifs will coexist. 69,108 In the present work, we have considered in all cases a bidentate dissociative bridge binding between the adsorbate and the substrate. The proton detached from the carboxylic-acid group is attached to a surface oxygen atom.…”
Section: A Characterization Of the Systemsmentioning
confidence: 99%
“…[15][16][17][18] Experimental Section Materials Aqueous solutions were prepared from water purified by use of a MilliQ purification system. Lithium perchlorate (98 % purity), 70 % perchloric acid (99.999 % purity), chloroplatinic acid (H 2 PtCl 6 ), titanium isopropoxide (97 % purity), isopropanol, hydroxypropylcellulose, zirconium isopropoxide, and Carbowax 20M were used as received from Sigma-Aldrich.…”
Section: Introductionmentioning
confidence: 99%